Glass fiber reinforced nylon-6/nylon-1012 composite material serves as automotive rearview mirror bracket - Guolong Wang; Lucheng Li; Peng Yang; Jun Chen (Next Materials)
In this study, nylon-6/nylon-1012 (PA6/PA1012) composites with varying glass fiber contents were prepared via twin-screw extrusion. The compatibility of PA6/PA1012 was significantly enhanced by the incorporation of 1.5 % ethylene-octene copolymer-grafted-maleic anhydride (POE-g-MAH), as evidenced by SEM analysis demonstrating uniform dispersion of PA1012 within the matrix. The addition of glass fiber (up to 30 wt%) led to a substantial enhancement in tensile strength, flexural strength, and thermal deformation temperature by 153 %, 305 %, and 275 %, respectively, in comparison with pure PA6. The optimized composite exhibited a melt flow index of 26.7 g/10 min (260°C/2.16 kg), which is significantly higher than that of ABS/ASA by 180 %, thereby enabling efficient molding of complex components. Moreover, the incorporation of anti-UV additives (UV-234/HS-944) resulted in the retention of over 79.3 % of impact strength after 500 h UV ageing, surpassing the performance of conventional ABS/ASA. The composite's low equilibrium water absorption (1.20 %) and high dimensional stability (HDT= 210 °C) underscore its suitability for automotive rearview mirror brackets. This study presents a novel strategy for the development of high-performance composites through interfacial optimization and functional additive design.